AN UNILATERAL SCLEROMALACIA PERFORANS IN YOUNG PATIENT MANAGED BY MYOCONJUNCTIVAL ENUCLEATION AND DERMIS FAT GRAFT: Poster Presentation - Case Report - Resident - ANNISA KARIMA; DELEFITRI LUTFI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Scleromalacia perforans is a disease that might compromise vision and globe integrity. The possible associations of systemic disease are autoimmune diseases such as rheumatoid arthritis, lupus, and Wegener's granulomatosis. Determining the underlying etiology in such cases also possess a great challenge to treat disease, especially in this case. Case Illustration : A 19-year-old female with a progressed protrusion of the left eye since she was 1 year old. Six years ago, she had redness, worsen protrusion, photophobia, tearing, and pain, but resolved without treatment. Her cousin had the same condition but refused to continue the examination. Visual acuityof the left eye was no light perception with 4x4 mm of corneal leukoma, and 360 degrees of anterior scleral ectasia covered with conjunctival neovascularization. USG showed posterior vitreous detachment and 28,9 mm axial length. Systemic examination found ANA test and HLA B27 were normal, positive hypermobility joint, and Rheumatologists ruled out the possibility of autoimmune disease. Myoconjuctival enucleation was performed with a dermis fat graft for cosmesis, and pathological examination showed nonspecific chronic inflammation. Discussion : A childhood-onset scleromalacia perforans with positive family history and hypermobility joints might be a sign of connective tissue disorder. Possible autoimmune diseases were ruled out by a rheumatologist. The genetic examinations may be necessary to establish the diagnosis. Conclusion : Scleromalacia perforans is rare yet it is strongly believed to have an association with systemic disease. Collaboration between ophthalmologists, rheumatologists, and geneticist is essential to manage this kind of case.